Language of employees of the Communist-era state security service in the Polish People’s Republic and the People’s Republic of Bulgaria (based on an analysis of “Bolek” and “Sabina” collaborators files) - Mazurkiewicz-Sułkowska, Julia (Specialized Languages in Intercultural Communication, 2020)
Releasing declassified files, reports, denunciations and other Communist-era secret service documents in the former socialist countries raises great controversies and emotions. The so-called “teczki” become an element of political maneuvering and power games. Reports from the informants and collaborators are usually the object of consideration for historians and archivists alike. However, there are virtually no linguistic analyses that characterize them. The paper is an attempt to investigate the language of secret service employees from a comparative perspective based on two collections of notes from Poland and Bulgaria.